Edukasi Pencegahan Stunting melalui Kelas Interaktif Pada Santriwati Pondok Sabilul Hasanah Banyuasin - Ningsih, Windi Indah Fajar; Ramdika, Sari Bema; Mukti, Retno Cahaya (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2025)
Santriwati (female Islamic boarding school student) are within the target age range for the 8000 HPK program, making it crucial to have sufficient protein intake to prevent stunting in future generations. Fish, being a good source of protein, is widely available in Islamic boarding schools due to its nutritional value and affordable price. However, protein intake among female students in these institutions often falls into the deficit category, primarily due to a lack of knowledge about the importance of fish as a protein source. This Community Service activity aims to enhance the knowledge of female students regarding nutrition and the role of protein through interactive classes. The interactive class includes nutrition presentation, games and coloring goodie bags with the slogan "". The activity was conducted at the Sabilul Hasanah Banyuasin Islamic boarding school involving 50 female students as respondents. The activity was carried out for 3 meetings in September 2024. The results of the paired showed a difference between knowledge before and after the educational activity was carried out (p <0.005). The female students showed great enthusiasm for the activity. Educational interventions through interactive sessions can effectively improve both the knowledge and enthusiasm of female students about the benefits of consuming fish.